Upaya Meningkatkan Prestasi Belajar Siswa Kelas V Sekolah Dasar dengan Model Pembelajaran Discovery Learning - Dewi Fiquroisyin (Universitas Sebelas Maret, 2020)
This Classroom Action Research aims to improve the learning achievement of fifth grade students at SDN Mangunsari by using the Discovery Learning learning model, where students are given the opportunity to find their own concepts and make discoveries in the learning process. While the teacher's role is to provide guidance. This study consisted of two cycles where each cycle consisted of four stages of activity, namely action planning, action implementation, observation, evaluation, data analysis and reflection of the results of the action. The second cycle of action was carried out by revising the learning techniques because the results of the actions in the first cycle had not reached the research objectives. Then the results of the second cycle of the written test also showed an increase in the percentage of students who got a test score >73 (KKM score), namely 16 students in cycle one to 33 students in cycle two. So it can be concluded that the use of discovery learning learning model can improve the learning achievement of fifth grade students at SDN Mangunsari